The Romanian Information Centre in the year of the Great Union Centennial (Confluenţe Bibliologice, 2019)
The Great Union of 1918 is the priceless good left to the descendants of the generation of the early twentieth century. The Great Union Centennial represents a moment of crossroads and a solemn occasion to renew the country project that brings us together, to rebuild solidarity between Romanians. The article is a retrospective of the events held in the  Romanian Information Centre during 2018, the year of the Great Union Centennial.
Keywords: Romanian Information Centre; the history of the Romanians; Great Union